Asuhan Keperawatan Pada Tn. T Keluarga Tn. T Dengan Gangguan Sistem Muskuloskeletal : Rheumatoid Arthritis Di Desa Purwodadi Kecamatan Tonjong Kabupaten Brebes - Azza Nurlaili Tsani; Tati Karyawati; Arisnawati (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that primarily affects the musculoskeletal system and often causes severe pain and functional limitations, especially among the elderly. This study aimed to provide a comprehensive overview of nursing care for a patient diagnosed with RA through a family-based approach. The research employed a descriptive qualitative method with a case study design conducted in a rural village in Brebes, Central Java. Data were collected through in-depth interviews, observation, and documentation. The results showed that the integration of non-pharmacological interventions, including warm compresses using ginger and lemongrass, and deep breathing techniques, significantly reduced pain intensity. Additionally, increased family involvement in caregiving, facilitated by structured health education, enhanced the patient's quality of life. This study confirms the importance of applying Dorothea Orem’s Self-Care Deficit Theory to support the independence and well-being of RA patients within their home environments. The findings suggest that community nurses should prioritize family empowerment in chronic disease management, particularly in areas with limited health access.